2016
DOI: 10.1093/rheumatology/kew272
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 regulates monocyte chemokine and chemokine receptor expression in Rheumatoid Arthritis

Abstract: Objective. To test the hypothesis that miR-155 regulates monocyte migratory potential via modulation of chemokine and chemokine receptor expression in RA, and thereby is associated with disease activity. Methods. The miR-155 copy-numbers in monocytes from peripheral blood (PB) of healthy (n = 22), RA (n = 24) and RA SF (n = 11) were assessed by real time-PCR using synthetic miR-155 as a quantitative standard. To evaluate the functional impact of miR-155, human monocytes were transfected with control or miR-155… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 27 publications
4
76
1
Order By: Relevance
“…The changes in cytokine levels we detected were a direct consequence of mir-155 over-expression, as no other stimulus was provided to the cells. These findings are supported by a recent study that reported a mir-155 mediated increase in the receptors for many of these chemokines [33]. Although we cannot rule out the possibility that the increase in detected cytokines could be due to increased numbers of surviving cells, rather than increased production per cell, the resulting wide-ranging influence of the induced mediators suggests a role for mir-155 in monocyte/macrophage-driven inflammatory processes in RA.…”
Section: Discussionsupporting
confidence: 86%
“…The changes in cytokine levels we detected were a direct consequence of mir-155 over-expression, as no other stimulus was provided to the cells. These findings are supported by a recent study that reported a mir-155 mediated increase in the receptors for many of these chemokines [33]. Although we cannot rule out the possibility that the increase in detected cytokines could be due to increased numbers of surviving cells, rather than increased production per cell, the resulting wide-ranging influence of the induced mediators suggests a role for mir-155 in monocyte/macrophage-driven inflammatory processes in RA.…”
Section: Discussionsupporting
confidence: 86%
“…S1A to D in the supplemental material). These cytokines have been shown to play an important role in monocyte migration and recruitment to the site of inflammation in leishmaniasis (36,37) and other diseases, such as HIV (38), rheumatoid arthritis, and atherosclerosis (39,40). Not surprisingly, chemical inhibition of CCR2 resulted in a reduction of parasitic burdens in L. donovani-infected miR155KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, proinflammatory effects of microRNA-155 were observed in monocytes. Transfection of monocyte cultures with microRNA-155 mimic led to increased proinflammatory cytokine and chemokine production and expression of the chemokine receptor CCR7, whereas IL-10 secretion and CCR2 expression were decreased [13,14]. These effects of microRNA-155 in monocytes and macrophages were attributed, at least in part, to a decreased repression of the suppressor of cytokine signaling-1 and SH2-containing inositol-5′-phosphatase 1, potent inhibitors of inflammation [5,6,13].…”
Section: Discussionmentioning
confidence: 99%